Tissue factor/factor VIIa induces cell survival and gene transcription by transactivation of the insulin-like growth factor 1 receptor - Åberg, Mikael; Eriksson, Oskar; Mokhtari, Dariush; Siegbahn, Agneta (Thrombosis and Haemostasis, 2014)
The insulin-like growth factor 1 receptor (IGF-1R) is known to promote survival and has also been implicated in the pathogenesis of several disease states, including cardiovascular disorders and cancer. Recently, we showed that binding of coagulation factor VIIa (FVIIa) to its receptor tissue factor (TF) protects cancer cells from TNF-related apoptosis inducing ligand (TRAIL)-induced apoptosis. Here we present evidence that this biological function of TF/FVIIa is dependent on the IGF-1R. IGF-1R inhibitors AG1024 and PPP as well as siRNA-mediated downregulation of IGF-1R, abolished the TF/FVIIa-mediated protection against TRAIL-induced apoptosis. Moreover, FVIIa rapidly induced a time- and concentration-dependent tyrosine phosphorylation of the IGF-1R in MDA-MB-231 breast cancer cells and in primary human monocytes, an event that was accompanied by IGF-1R chromatin binding and gene transcription. We hereby present novel evidence of a cross-talk between the coagulation and IGF-1R signalling systems, and propose that the IGF-1R is a key player in mediating TF/FVIIa-induced cell survival.
Keywords: Tissue factor; FVIIa; Apoptosis; IGF-1R; Cell signalling